Perception and Motivation of Female and Male Students Toward STEM in Indonesia - Septian Karyana; Elly Herliani (SEAQIS Journal of Science Education, 2021)
The aim of this research is to find out the differences of male and female lower secondary school students on the aspects of perception, motivation, and interest in the field of STEM. The sample of this study consists of 370 middle school students in various province in Indonesia who had experience in STEM learning with teacher who had participated SEAQIS STEM training. The instrument used in this study was five scales Likert of SEAQIS STEMs Survey (SS-STEMs), which cover perception and motivation toward Science, Technology and Engineering as well as Mathematics. The instrument was validated by Rasch Model approach using Winstep v 3.7 and was found that it compatible with the model. Winstep software v3.73 was also used for data analysis. It was found that: (1) There is a significant difference between male and female students in the aspects of perception toward mathematics subjects; (2) There is no significance difference between male and female students in the aspects of motivation towards all subjects.